2011
DOI: 10.4028/www.scientific.net/amm.66-68.1505
|View full text |Cite
|
Sign up to set email alerts
|

Rubber Joint for Fatigue Crack Factors Numerical Analysis of Certain Vehicle

Abstract: The main factor of rubber fatigue was stress field. But the way is not sensitive in many cases. To clarify which factors were the main for predict the locations of fatigue crack, we analyzed the factors of stress field and strain field of rubber joint, and relations between the factors and the locations of fatigue crack, using 3D FE simulation. The result showed stress concentration was not sensitive to predict the locations of fatigue crack. The locations are close to strain concentration of rubber joint. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The hardness of outsole materials is indicated with Shore A Hardness (HA, º), which is generally used to measure the hardness of rubber products; the greater its value, the higher the hardness ( Zhao et al, 2015 ). The equation of Elastic modulus (E) and outsole hardness (HA) is as follows ( Wang et al, 2011 ): …”
Section: Methodsmentioning
confidence: 99%
“…The hardness of outsole materials is indicated with Shore A Hardness (HA, º), which is generally used to measure the hardness of rubber products; the greater its value, the higher the hardness ( Zhao et al, 2015 ). The equation of Elastic modulus (E) and outsole hardness (HA) is as follows ( Wang et al, 2011 ): …”
Section: Methodsmentioning
confidence: 99%
“…(1) E is the elastic modulus of rubber material, σ is the pressure per unit area and ε is the shape variable of a material under specific pressure. Combine with calculation formula of soft hardness index [15,16]. E=(15.75+2.15HA)/(100-HA).…”
Section: Methodsmentioning
confidence: 99%
“…After comparing the results of the experiments and simulations, the most suitable strain energy function hyperelastic material model of the rubber fender was determined finally. Wang et al [14] analyzed the factors of the stress field and strain field of rubber joints and the relationship between these factors and the location of fatigue cracks through threedimensional finite element simulation. The results showed that the stress concentration is not sensitive to the prediction of a fatigue crack's location, and the method of using strain concentration to predict the fatigue crack location of rubber joints was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…where ε 1 is the principal strain (engineering strain) in this direction. Substituting formula (13) and formula (14) into formula (11), it can be obtained that:…”
mentioning
confidence: 99%